Why Innovation is Not Always Good: Innovation Discourses and Political Accountability. (September 2014) - Crivits, M.; de Krom, Michiel P.M.M.; Dessein, J.; Block, T.
Innovation is rarely considered a point of contention in agriculture. It invariably seems to denote some type of intrinsically desired newness associated with effective commercialization of a new technology, idea or organizational form. However, once innovation is considered as something happening within a network or 'system' of interdependent actors, it becomes clear that different interpretations and appropriations of innovation are co-evolving in a competitive framework. Although the authors acknowledge the importance of collective learning processes as a basis for overcoming barriers to innovation in networks, they caution that such a view of innovation insufficiently conceptualizes the role of power. To gain insight into how more inclusive innovation processes can be built, the authors evaluate how farmers' interests can be articulated and how innovation networks can be held accountable to ensure fair representation of the diversity of farmers' views. They propose a framework anchored in deliberative democratic theory that attributes significant transformative power to deliberation in decision making. The framework is based on the concept of 'discursive accountability', in which representation is related to a procedure guaranteeing a maximum of relevant discourses to be articulated within collective decision making in governance networks. The authors substantiate its utility through a case study of pig farming in Flanders, using discourse analysis to reveal how the discursive framings of farmers reflect an ongoing tension between the linear and the participatory innovation discourses. They complement this analysis with an assessment of the collective outcomes of a series of 'dialogue days' in the Flemish pig sector.